Evaluating Stroke Code Activation Pathway in Emergency Departments study. (18th July 2022) - Ebker‐White, Anja; Dinh, Michael; Paver, Ian; Bein, Kendall; Tastula, Kylie; Gattellari, Melina; Worthington, John
Abstract: Objectives: To describe the clinical characteristics and outcomes of Code Stroke activations in an ED and determine predictors of a final diagnosis of stroke or transient ischemic attack (TIA) diagnosis. Methods: This was a retrospective analysis of Code Stroke activations through an ED over 2 years at a quaternary stroke referral centre. Stroke Registry data was used to identify cases with clinical information abstracted from electronic medical records. The primary outcome was a final diagnosis of acute stroke or TIA and the secondary outcome was access to reperfusion therapies (thrombolysis and or endovascular clot retrieval). Results: The study analysed data from 1354 Code Stroke patients in ED. Of all Code Strokes, 51% had a stroke or TIA diagnosis on discharge. Patient characteristics independently associated with increased risk of stroke were increasing age, pre‐arrival notification by ambulance, elevated BP or presence of weakness or speech impairment as the initial presenting symptoms. Dizziness/vertigo/vestibular neuritis were the most common alternative diagnoses. One hundred and thirty‐five patients (10%) underwent reperfusion therapy. Pre‐arrival notification by ambulance was associated with higher proportion of eventual stroke/TIA diagnosis (68% vs 46%, P  < 0.001) and significantly lower door to CT and door to needle times for patients undergoing thrombolysis. Conclusions: In a cohort of patients requiring Code Stroke activation in an ED, increased age, systolic blood pressure and weakness and speech impairment increased the risk of stroke. Prehospital notification was associated with lower door to needle times for patients undergoing thrombolysis. Abstract : This is a retrospective study looking at ED patients who have undergone a stroke call. The objective of the study was to describe the clinical characteristics and outcomes of Code Stroke activations in an emergency department and determine predictors of a final diagnosis of stroke or TIA diagnosis.